Thermo-Acoustic Properties of a Burner with Axial Temperature Gradient: Theory and Experiment. (March 2013) - Kosztin, Béla; Heckl, Maria; Müller, Roel; Hermann, Jakob
This paper presents a model for thermo-acoustic effects in a gas turbine combustor. A quarter-wavelength burner with rectangular cross-section has been built and studied from an experimental and theoretical perspective. It has a premixed methane-air flame, which is held by a bluff body, and spans the width of the burner. The flame is compact, i.e. its length is much smaller than that of the burner. The fundamental mode of the burner is unstable; its frequency and pressure distribution have been measured. The complex pressure reflection coefficients at the upstream and downstream end of the burner were also measured. For the theoretical considerations, we divide the burner into three regions (the cold pre-combustion chamber, the flame region and the hot outlet region), and assume one-dimensional acoustic wave propagation in each region. The acoustic pressure and velocity are assumed continuous across the interface between the precombustion chamber and flame region, and across the interface between the flame region and outlet region. The burner ends are modelled by the measured pressure reflection coefficients. The mean temperature is assumed to have the following profile: uniformly cold and uniformly hot in the pre-combustion chamber and outlet region, respectively, and rising continuously from cold to hot in the flame region. For comparison, a discontinuous temperature profile, jumping directly from cold to hot, is also considered. The eigenfrequencies are calculated, and the pressure distribution of the fundamental mode is predicted. There is excellent agreement with the experimental results. The exact profile of the mean temperature in the flame region is found to be unimportant. This study gives us an experimentally validated Green's function, which is a very useful tool for further theoretical studies.